Principle of vat neutrality and the reverse charge mechanism - Teresa Famulska; Beata Rogowska-Rajda (e-Finanse: Financial Internet Quarterly, 2018)
The principle of VAT neutrality is among the fundamental characteristics of this tax. It is implemented through reduction of VAT output by the amount of VAT input. The right of deduction constitutes an integral part of the VAT mechanism and is intended to free the entrepreneur entirely from the burden of VAT paid for the goods and services purchased within the framework of business activity. However, in certain situations it is possible to shift the obligation to pay VAT to the customer being a taxable person by introducing a reverse charge mechanism. The purpose of the article is to identify the relationship between the implementation of the principle of VAT neutrality and the reverse charge mechanism. The conducted analysis of the essence and functioning of the reverse charge and the detailed findings drawn on its basis allow us to conclude generally that this mechanism does not affect implementation of this principle.
Keywords: H21; H25; H32; 330; VAT; input VAT; output VAT; principle of VAT neutrality; reverse charge